Development of a patient decision aid for the treatment of localised prostate cancer: a participatory design approach. Issue 7 (16th February 2016) - Al‐Itejawi, Hoda HM; van Uden‐Kraan, Cornelia F; Vis, André N; Nieuwenhuijzen, Jakko A; Hofstee, Myrna JA; van Moorselaar, Reindert Jeroen A; Verdonck‐de Leeuw, Irma M
Abstract : Aims and objectives: To develop a patient decision aid and to prepare an overview of requirements for implementation. Background: We developed a decision aid that fits the preferences of patients and health care professionals to ensure adequate uptake in clinical practice. Design: A participatory design approach was used to acquire insight into preferences regarding the content and design of a decision aid and into barriers and aspects of the decision aid that facilitate implementation in clinical practice. Methods: Three focus group interviews with patients, their partners and health care professionals were conducted. A prototype of the decision aid was developed and presented to patients ( n  = 14) and health care professionals ( n  = 13) in semi‐structured interviews. Patients ( n  = 5) participated in a usability study. Data were analysed by two independent coders. Results: Health care professionals considered medical information on treatments and side effects as the most important aspect to be included in the decision aid. Patients also focused on nonmedical considerations, such as location. Both expected the decision aid to support patients in making a treatment choice. According to health care professionals, the oncology nurse was the most suitable to discuss the decision aid with patients, while some patients preferred to discuss the patient decision aid with the urologist. The main barrier to implementation of the decision aid was said to be the expectation that it is time and money consuming, while the incorporation of the decision aid into clinical guidelines and basing the content on these guidelines, would promote implementation. Conclusions: By using a participatory design approach a patient decision aid was designed to meet patients' and health care professionals' needs. Insight was also gained on requirements for implementation. Relevance to clinical practice: Wide‐scale implementation of decision aids is desirable. An overview is provided of requirements for implementation to successfully incorporate a decision aid into clinical practice.